Identifikasi Konsep Fisika pada Kearifan Lokal Kesenian Tongklek di Indonesia - Nasution, Nabilla Nur Almaida; El Shinta, Chamila; Nugraha, Via Aprilia; Pramesti, Ardhia; Suliyanah, Suliyanah; Saputra, Oka; Deta, Utama Alan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Indonesia is a country with cultural diversity that has been passed down from generation to generation. One of these cultures is the Tongklek art originating from Tuban Regency, East Java. In Tongklek art, all musical instruments used can be associated with the application of physics concepts. However, due to limited human resources, the study of the physics concepts contained in the art of Tongklek has received little attention. This study aims to identify the concept of physics in the local wisdom of Tongklek in order to increase public knowledge. In this study using a descriptive research method with a qualitative approach. The analysis technique used is data reduction. Based on the results of the research, it was found that the Tongklek art is a type of traditional art in the form of music art found in Tuban Regency, East Java. Tongklek art is a type of art in which there are several musical instruments, among the musical instruments used are kentongan, xylophone, bonang/kenong, gong suwuk, blunt gong, gong jengur/jegluk, drums, and plastic drums. In every musical instrument in the Tongklek art there is a concept of physics, namely the material of sound waves, especially organ pipes. The source of the sound of the Tongklek art, on average, comes from musical instruments that have a certain volume, there are forms where all fields are closed, there are also some of these things which are named as air columns as the source of the vibrations.